The Influence of TikTok Usage Intensity and Type of Content Consumed on Gen-Z's Self-Esteem and Mental Health - Mely Nadia (Jurnal EduHealth, 2025)
The rise of social media has transformed the way companies and businesses connect with consumers. One approach now widely used is content marketing, which seeks to capture attention and build engagement with audiences through the presentation of relevant, engaging, and valuable content. This study aims to analyze the influence of TikTok usage intensity and the type of content consumed on the self-esteem and mental health of Generation Z. The research is motivated by the increasing popularity of TikTok as a dominant social media platform among adolescents and young adults, raising psychological concerns that require deeper investigation. This study employs a quantitative approach using a survey method with 200 respondents aged 15–25 years who are active TikTok users. The instruments were measured using a 5-point Likert scale to assess TikTok usage intensity, content type, self-esteem (Rosenberg Self-Esteem Scale), and mental health (GHQ-12). Data were analyzed using multiple linear regression. The results indicate that TikTok usage intensity has a negative and significant effect on self-esteem and a positive and significant effect on mental health symptoms. This suggests that higher usage intensity leads to lower self-esteem and poorer mental well-being. Conversely, the type of content consumed has a positive and significant effect on self-esteem and a negative and significant effect on mental health, meaning that exposure to more positive content improves psychological conditions. Simultaneously, both TikTok usage intensity and content type significantly affect self-esteem and mental health among Generation Z. These findings demonstrate that TikTok has a dual psychological impact depending on usage duration and the quality of consumed content. The results are expected to contribute to digital literacy programs and psychological support initiatives for Generation Z.